From temples to garden estates and academies: landscape transformation of Suzhou during the 13th-16th centuries and beyond - Mu, Pania Yanjie (Routledge research on gardens in history, 2025)
"How did the temple-scape of Suzhou transform into garden-scape during the 13th to 16th centuries? This book investigates the landscape evolution of China during the Yuan-Ming socio-political transformation and provides a previously unrepresented Buddhist and hydraulic history of Chinese gardens. Utilizing historical GIS mapping and 3D architectural modelling, the research uncovers spatial strategies employed by monks, the gentry, and the government. It argues that by seizing hydraulic estates from Buddhists, the gentry and government rose as landed class and cultural elites, establishing the literati garden. Yuan temples featured a mound-field-river topography which reclaimed urban wetlands. In temples such as Shizi Lin, scenes were crafted as Chan gong'ans to support Buddhist practice towards enlightenment, underpinning a monastic architectural transformation in the 14th century. In the Ming dynasty, the gentry and government exploited the hydro-topography while erasing Buddhist traces by converting temples into gardens. The book forms a theoretical model of triangulating the garden practice with socio-hydro spaces and advocates a new garden history enabled by historical mapping and modelling. This book is aimed at students and scholars of East Asian history, temples and gardens, and landscape architecture and design"--